Detection of melamine in milk using molecularly imprinted polymers–surface enhanced Raman spectroscopy. (1st June 2015) - Hu, Yaxi; Feng, Shaolong; Gao, Fang; Li-Chan, Eunice C.Y.; Grant, Edward; Lu, Xiaonan
Highlights: Overall analysis time for this biosensor is ∼18 min, including sample pretreatment. MIPs provides good separation and enrichment of melamine from whole milk samples. LOD and LOQ was 0.005 mmol L −1 melamine in whole milk. This biosensor has the potential to be applied in dairy industry. Abstract: A novel biosensor combining molecularly imprinted polymers and surface-enhanced Raman spectroscopy (MIPs–SERS) determines melamine in whole milk. MIPs were synthesized by bulk polymerization of melamine (template), methacrylic acid (functional monomer), ethylene glycol dimethacrylate (cross-linking agent) and 2, 2′-azobisisobutyronitrile (initiator). Static and kinetic adsorption tests validated the use of MIPs to efficiently separate and enrich melamine from whole milk. Silver dendrite nanostructure served as SERS-active substrate for signal collection. Principal component analysis and hierarchical cluster analysis segregated Raman signatures of whole milk samples with different melamine concentrations. Regression models showed a good linear relationship ( R 2  = 0.93) between the height of melamine SERS band (at 703 cm −1 ) and melamine concentration in the range from 0.005 mmol L −1 to 0.05 mmol L −1 . The limit of detection and limit of quantification were 0.012 mmol L −1 and 0.039 mmol L −1, confirming the high sensitivity of this biosensor to accurately determine melamine in whole milk. Simple sample pretreatment reduced full analysis time to determine melamine in whole milk to less than 20 min.